2016
DOI: 10.1039/c5cp06379e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation promotes Al(iii) binding to proteins: GEGEGSGG as a case study

Abstract: Aluminum, the third most abundant element in the Earth's crust and one of the key industrial components of our everyday life, has been associated with several neurodegenerative diseases due to its ability to promote neurofilament tangles and β-amyloid peptide aggregation. However, the experimental characterization of aluminum speciation in vivo is a difficult task. In the present study, we develop a theoretical protocol that combines molecular dynamics simulations, clustering of structures, and density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…Hollender et al 87 demonstrated that phosphorylation increases the affinity of peptides for aluminum and that this interaction affects the secondary structure, using multinuclear NMR and CD spectroscopy applied to an octapeptide with one phosphorylated serine site. Computational results in our group 88 confirmed the increase in metal affinity upon phosphorylation. In the present work, we have considered a more complex system, NF13, and its serine-phosphorylated derivatives.…”
Section: Biological Implications In the Context Of Metal Ion Hypothesissupporting
confidence: 56%
See 1 more Smart Citation
“…Hollender et al 87 demonstrated that phosphorylation increases the affinity of peptides for aluminum and that this interaction affects the secondary structure, using multinuclear NMR and CD spectroscopy applied to an octapeptide with one phosphorylated serine site. Computational results in our group 88 confirmed the increase in metal affinity upon phosphorylation. In the present work, we have considered a more complex system, NF13, and its serine-phosphorylated derivatives.…”
Section: Biological Implications In the Context Of Metal Ion Hypothesissupporting
confidence: 56%
“…These calculations have proved that phosphorylated peptides show larger interaction energy than non-phosphorylated counterparts. 49,77,88 However, only a few structures show comparable interaction energies to citrate. 49 On the other hand, properly determining the last two conditions requires long molecular dynamics simulations to obtain properly converged ensembles of these systems.…”
Section: Pccp Papermentioning
confidence: 99%
“…This type of binding motif would lead to a dramatic change on the secondary structure of the protein, altering its conformation and provoking its denaturation. However, the existence of this type of binding motif is difficult to reconcile with previous experimental [12,14] and theoretical studies [15,16] that have unequivocally established the propensity of aluminum to interact with amino acid sidechains with Al-O bonds of mainly electrostatic nature.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…For instance, in the case of the experimentally and theoretically studied GEGEGSGG octapeptide we obtain different G values depending on the coordination of aluminum. [15] We have chosen three paradigmatic cases: i) N1-GEGEGSGG where aluminum interacts with only one aspartate sidechain, -33.7 kcal/mol, N6-GEGEGSGG which shows one aspartate sidechain in the first coordination shell and a second carboxylate group in the second coordination sphere, -67.9 kcal/mol, and finally, P1-GEGEGSGG with a phosphorylated serine coordinating aluminum, -78.2 kcal/mol. All cases show a more favorable interaction than with the models in which aluminum is directly interacting with the peptide backbone.…”
Section: Interaction With Amino Acid Sidechainsmentioning
confidence: 99%
“…9 On the other hand, molecules containing phosphate groups are also a likely target for interacting with the cation. 8,[10][11][12][13][14] Due to the variety of cellular processes in which molecules containing phosphate groups are present (ATP, phosphorylated proteins, sugar phosphates, DNA, etc. ), this high affinity to form Al(III)-phosphate compounds could disrupt key processes of the cell metabolism.…”
Section: Introductionmentioning
confidence: 99%